The Lessons Learned From An Airline In-Flight Entertainment Graphical User Interface Project. - Wake, Thomas (2008)
There is a recent history of airline acquisitions and mergers as the industry has consolidated after several turbulent events outside of its control. During February 2007 Epsilon (a UK based airline) acquired and decided to integrate with Zeta (also a UK based airline). One of the projects related to this integration was the re-branding of the Zeta In-Flight Entertainment (IFE) product. Due to a franchise agreement with Eta (a third UK based airline), the Zeta IFE systems were Eta branded along with the rest of the aircraft's livery and interior decoration. The re-branding of the IFE was one project in a larger programme to remove all traces of the Eta brand from these aircraft and to replace it with the Epsilon brand.